Musik Dan Trance: Studi Kasus Seni Pertunjukan Jaranan “Turangga Muda Budaya” Tulungagung, Jawa Timur - Septiya, Marenda Adhi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Jaranan is a synthesis art between music and dancing in wich has a value of ritual. there is a diffrence between jaranan art and the others art. in the jaranan art, the actor experinces trance or in java language called